The Effect of Perceived Ease of Use, Perceived Usefulness, and Compatibility on the Intention to Use the Samsat Digital National (SIGNAL) Application in Padang - Alifian Riza Ahmad; Reno Fithri Meuthia; Ferdawati (International ABEC, 2022)
The purpose of this research is to investigate the intention to use of application named Samsat DigitalNasional (SIGNAL) in Padang. The theory used in this research is the Technology Acceptance Model andDiffusion of Innovation within the variable of perceived ease of use, perceived usefulness, compatibility asindependent variables, and intention to use as dependent variables. The population of this study was motor vehicletaxpayers in Padang. The sampling method used was convenience sampling with a total sample are 98respondents. Data was collected by distributing the questionnaires via social media platforms and printed. Theresult of this study indicates that the perceived ease of use and compatibility significantly affects the intention touse the SIGNAL application in Padang. Otherwise, the perception of usefulness did not affect the intention to usethe SIGNAL application in Padang. Furthermore, this study can be a reference for Samsat Padang and KorlantasPolri to socialize more regarding the use of the SIGNAL application to the vehicle taxpayer in Padang